Factors influencing public health engagement in alcohol licensing in England and Scotland including legal and structural differences: comparative interview analysis - Niamh Fitzgerald; Andrea Mohan; Richard Purves; Rachel O’Donnell; Matt Egan; James Nicholls; Nason Maani; Maria Smolar; Andrew Fraser; Tim Briton; Laura Mahon (Public Health Research)
Background Greater availability of alcohol is associated with higher consumption and harms. The legal systems, by which premises are licensed to sell alcohol in England and Scotland, differ in several ways. The ‘Exploring the impact of alcohol licensing in England and Scotland’ study measured public health team activity regarding alcohol licensing from 2012 to 2019 and identified seven differences between England and Scotland in the timing and type of activities undertaken. Objectives To qualitatively describe the seven previously identified differences between Scotland and England in public health approaches to alcohol licensing, and to examine, from the perspective of public health professionals, what factors may explain these differences. Methods Ninety-four interviews were conducted with 52 professionals from 14 English and 6 Scottish public health teams selected for diversity who had been actively engaging with alcohol licensing. Interviews focused primarily on the nature of their engagement (n = 66) and their rationale for the approaches taken (n = 28). Interview data were analysed thematically using NVivo. Findings were constructed by discussion across the research team, to describe and explain the differences in practice found. Findings Diverse legal, practical and other factors appeared to explain the seven differences. (1) Earlier engagement in licensing by Scottish public health teams in 2012–3 may have arisen from differences in the timing of legislative changes giving public health a statutory role and support from Alcohol Focus Scotland. (2) Public Health England provided significant support from 2014 in England, contributing to an increase in activity from that point. (3) Renewals of statements of licensing policy were required more frequently in Scotland and at the same time for all Licensing Boards, probably explaining greater focus on policy in Scotland. (4) Organisational structures in Scotland, with public health stakeholders spread across several organisations, likely explained greater involvement of senior leaders there. (5) Without a public health objective for licensing, English public health teams felt less confident about making objections to licence applications without other stakeholders such as the police, and instead commonly negotiated conditions on licences with applicants. In contrast, Scottish public health teams felt any direct contact with applicants was inappropriate due to conflicts of interest. (6) With the public health objective in Scotland, public health teams there were more active in making independent objections to licence applications. Further in Scotland, licensing committee meetings are held to consider all new applications regardless of whether objections have been submitted; unlike in England where there was a greater incentive to resolve objections, because then a meeting was not required. (7) Finally, Scottish public health teams involved the public more in licensing process, partly because of statutory licensing forums there. Conclusions The alcohol premises licensing systems in England and Scotland differ in important ways including and beyond the lack of a public health objective for licensing in England. These and other differences, including support of national and local bodies, have shaped opportunities for, and the nature of, public health engagement. Further research could examine the relative success of the approaches taken by public health teams and how temporary increases in availability are handled in the two licensing systems. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Public Health Reseacrh programme as award number 15/129/11. Plain language summary When alcohol becomes more widely available, harms tend to increase. In England and Scotland, this availability is controlled by local councils. They ‘licence’ shops, bars and other venues to allow them to sell alcohol. Local health teams, including doctors, often advise councils on licensing. In earlier work, we found seven differences in what Scottish and English health teams do on licensing. In this study, we explore these seven differences and why they came about. To do this, we interviewed 94 professionals working in public health across both countries. Scottish health teams got involved in licensing earlier than in England. This was partly because of when certain laws changed. Also, they were helped earlier by national organisations that try to reduce harm from alcohol. Scottish teams were more involved in local policies on licensing. This was probably because these policies changed more often in the Scottish system. Scottish teams involved the public more. This was partly because Scottish councils must set up ‘local licensing forums’. Scottish teams also objected more often to licence applications. They generally felt that they could be more actively involved, because of a law in Scotland that says licensing must protect public health. This law does not apply in England. In England, health teams were more likely to talk to businesses that wanted licences. They were less likely to try to block applications. When they agreed changes to applications with businesses instead of objecting, fewer formal licensing meetings were needed. This was not the case in Scotland. Also, Scottish teams did not feel it was okay for them to talk to businesses. In summary, there are important differences in licensing law between Scotland and England. These matter for how health teams in the two countries engage with local councils, businesses and the public on licensing matters.